(untitled) (International Journal of Studies in Nursing, 2026)
International Journal of Studies in Nursing; Vol. 7, No. 2; 2022 ISSN 2424-9653 E-ISSN 2529-7317 Published by July Press Ray, A. (Ed.). (2021). Empowering Midwives and Obstetric Nurses. London: IntechOpen Omona Kizito1 1 Lecturer, Uganda Martyrs University, Faculty of Health Sciences, Kampala, Uganda Correspondence: Dr Omona Kizito, Lecturer, Uganda Martyrs University, Faculty of Health Sciences, Kampala, Uganda. Received: March 12, 2022 Accepted: April 26, 2022 Online Published: June 19, 2022 doi:10.20849/ijsn.v7i2.1195 URL: https://doi.org/10.20849/ijsn.v7i2.1195 In order to equip practitioner midwives and nurses, I find „Empowering Midwives and Obstetric Nurses‟ a book to be treasured. This is more especially when it comes to supporting learning and preparing readers for the challenges faced in contemporary healthcare. This book with 192pages and twelve chapters is a treasure. The first chapter, „Empowering Midwives and Obstetric Nurses‟ has very impressive definitions. It contains this noteworthy quote: “The term midwifery has been coined from two Old English words “mid “which means with and “wif” which comes from woman. Taken together the word midwife means a person who is with the woman. This person could belong to any gender provided the person is with the woman during pregnancy as well as the whole process of childbirth and thereafter: probably the most eventful and crucial part of a woman’s life (p1).” The second chapter talks about vaginal delivery, pointing out all the indications and contraindications to vaginal delivery. The third chapter is about preterm labour, in particular, delving in the science behind tocolysis in preterm labour (table 1) among other details of the chapter. Also, interesting in the chapter is the role of antibiotic administration in preterm labour, said to reduce the time to delivery and the incidence of chorioamnionitis in preterm premature rupture of membranes. Chapter four is about identification and management of high risk complications during postnatal period by ground level workers. In this, High Risk mothers in the postnatal period have been defined as those mothers who are at the risk of their lives because of the complication occurring in the postnatal periods. Chapter five, six and seven are about challenges in the delivery room, normal puerperium and principles of midwifery care during virulent outbreaks respectively. Chapter eight discusses the impact of Antenatal Care in Maternal and Perinatal Health, pointing out the launch of a safe motherhood initiative in 1987 by the World Health Organization in a conference in Nairobi, Kenya (Starrs, 2006). The event aimed to raise awareness about the numbers of women dying each year from complications of pregnancy and childbirth, and to challenge the world to do something. Chapter nine is about diagnosing congenital abnormality using ultrasound during antenatal care Chapter ten discusses effect of Community-Based intervention on institutional delivery in Ethiopia. Interesting community interventions such as the adaptation of cultural practices at the health facility level for example preparation of “maternal waiting home”, making the service free of charge and the provision of charge-free transport service for pregnant women during labor and delivery have been discussed. Chapter eleven is about domestic violence in pregnant women and how to manage the vice. This reinforces the recent study on domestic violence and its relationship with quality of life in pregnant women (Naghizadeh, Mirghafourvand & Mohammadirad, 2021). The twelveth Chapter talks about poverty, reproductive health and public health policies in Chile. Conclusively, having reviewed the book in its entirety, I find it worth recommending for peer readership. 51